How to Succeed in Fellowship Acquisition: A Survey of Pathology Residents - Etan Marks DO; Michael B. Prystowsky MD, PhD; Amy S. Fox MD, MS (Elsevier, 2019)
Medical school curricula limit students' exposure to pathology practice while pathology subspecialty training programs require residents to apply for fellowships as early as the end of their first year of training. Thus, limited exposure to pathology practice creates significant confusion and anxiety, often making the fellowship application process premature. Additionally, early focus on subspecialty training in order to acquire a fellowship adds to the initial lack of emphasis on general pathology training. We prepared a voluntary online survey with questions developed through focus groups and advice from an expert in survey design to determine which fellowships are desired and how successful residents are in their pursuit of these fellowships. The survey was distributed through the Pathology Residency Program Directors' (PRODS) listserv. Answers were solicited from pathology trainees throughout the entire training cycle. There were 141 (4.6% response rate) total respondents with each postgraduate year represented. One hundred twenty-two (95%) of 129 residents plan on completing 1 or 2 fellowships after residency training. Encouragingly, 94 (75%) of 126 pathology residents attained their desired specialty fellowship. However, 32 (32%) of 99 residents who acquired at least one fellowship chose a general surgical pathology fellowship. Furthermore, 33 (24%) respondents had already decided to pursue a specific specialty while still in medical school. An additional 32 (23%) came to their decision during postgraduate year 1. Therefore, although most residents are successful in attaining their desired fellowship, further research is needed to understand the effect of early commitment to a subspecialty and its impact on pathology education.